Molecular epidemiology and carbapenem resistance characteristics of Acinetobacter baumannii causing bloodstream infection from 2009 to 2018 in northwest China - Gu, Yihai; Zhang, Wei; Lei, Jine; Zhang, Lixia; Hou, Xuan; Tao, Junqi; Wang, Hui; Deng, Minghui; Zhou, Mengrong; Weng, Rui; Xu, Jiru (Frontiers in Microbiology, 2022)
Bloodstream infection (BSI) caused by Acinetobacter baumannii poses a serious threat to health and is correlated with high mortality in patients with hospital-acquired infections, so the molecular epidemiology and antimicrobial resistance characteristics of this pathogen urgently need to be explored. A. baumannii isolates from BSI patients were collected in three tertiary hospitals in northwest China from 2009 to 2018. Antimicrobial susceptibility testing was used to determine the MICs of the A. baumannii isolates. Whole-genome sequencing based on the Illumina platform was performed for molecular epidemiological analyses and acquired resistance gene screening. The efflux pump phenotype was detected by examining the influence of an efflux pump inhibitor. The expression of efflux pump genes was evaluated by RT-PCR. In total, 47 A. baumannii isolates causing BSI were collected, and they presented multidrug resistance, including resistance to carbapenems. Clone complex (CC) 92 was the most prevalent with 30 isolates, among which a cluster was observed in the phylogenetic tree based on core genome multi-locus sequence type, indicating the dissemination of a dominant clone. BSI-related A. baumannii isolates normally harbour multiple resistance determinants, in which the oxacillinase genes were most common. In addition to the intrinsic blaOXA-51 family, these A. baumannii isolates also harbour blaOXA-23, which is encoded within the Tn2006, Tn2008 or Tn2009 transposon structures, followed by blaOXA-72 and blaOXA-181, which mediated carbapenem resistance. The transfer of blaOXA-72 was suggested by XerC/D site-specific recombination. The AdeABC efflux pump system was correlated with carbapenem resistance, as evidenced by the high expression of the encoding genes. Both the clone dissemination and carbapenem resistance mediated by oxacillinase or efflux pump urge the effective strategy of hospital infection control.